Pharmacological Study of Cefazolin During Intermittent and Continuous Infusion: a Crossover Investigation in Humans - Thys, J. P. (1976)
Levels of cefazolin were determined in plasma, urine, bile, and cerebrospinal fluid in humans after a bolus intravenous injection and during a controlled, continuous intravenous infusion. All the patients were studied in a steady-state and crossover fashion. In plasma, the mean peak level after bolus injection (1.5 g) studied in 12 patients was 206.5 μg/ml; during continuous infusion (6 g daily), the mean level remained stable at 52.6 μg/ml. With bolus injection and continuous infusion, respectively, 89.7 and 86.3% of the administered dose of cefazolin were excreted in the urine of nine patients over the 6-h period considered. The levels of cefazolin in common bile duct bile were studied in six cholecystectomized patients. In bile collected during the two 3-h periods of the experiment, the mean concentration of the drug in the bile after bolus injection was 66.9 and 22.0 μg/ml, respectively; during continuous infusion, the corresponding biliary levels were 50.7 and 51.3 μg/ml, respectively. In four neurosurgical patients with an intraventricular catheter, neither bolus injection nor continuous infusion resulted in a demonstrable concentration of cefazolin in the cerebrospinal fluid. The continuous intravenous administration of cefazolin might have some advantage over the intravenous bolus intermittent injections. In plasma, the area under the curve is greater with continuous infusion than with bolus injection. In bile, the levels of cefazolin are more sustained with continuous infusion than with bolus injection. This approach to intravenous administration of cefazolin deserves more pharmacological and clinical trials.